The GLP-1 receptor agonist, liraglutide, fails to slow disease progression in SOD1G93A and TDP-43Q331K transgenic mouse models of ALS - Amy Keerie (Nature Portfolio, 2021)
Abstract GLP-1 receptor agonists used for the treatment of diabetes, have shown some neuroprotective effects in cellular and animal models of Alzheimer’s disease (AD) and Parkinson’s disease (PD). There are currently few studies investigating GLP-1 receptor agonists in the treatment of ALS, where these neuroprotective effects may be beneficial. Here we investigate the effects of liraglutide, a GLP-1 receptor agonist, in two well characterised transgenic mouse models of ALS (SOD1G93A and TDP-43Q331K) to determine if liraglutide could be a potential treatment in ALS patients. Doses of liraglutide previously shown to have efficacy in AD and PD mouse models were used. Behavioural testing was carried out to ascertain the effect of liraglutide on disease progression. Immunohistochemical analysis of tissue was used to determine any neuroprotective effects on the CNS. We found that liraglutide dosed animals showed no significant differences in disease progression when compared to vehicle dosed animals in either the SOD1G93A or TDP-43Q331K mouse models of ALS. We also observed no changes in motor neuron counts or glial activation in lumbar spinal cords of liraglutide treated mice compared to vehicle dosed mice. Overall, we found no evidence to support clinical evaluation of liraglutide as a potential candidate for the treatment of ALS.